Analisis Swot (Strengths, Weaknesses, Opportunities, And Threats) Pada Peningkatan Pelayanan Transportasi Umum di Surabaya - Feri; Indah Murti; Yusuf Hariyoko (Public Sphere Review, 2024)
The city of Surabaya has a lot of public transportation that is easy for the public to find, however problems are still often encountered such as traffic jams, inappropriate travel routes, etc. Therefore, strategic planning based on analysis of internal and external environmental conditions is very important to improve transportation services in Surabaya. This study aims to determine the community's perspective on SWOT analysis (Strengths, Weaknesses, Opportunities and Threats) on improving public transportation services in Surabaya. The approach used is qualitative, based on evaluation of external factors (EFE) and internal factors (IFE) with describing in accordance with the theory of the five dimensions of service quality from Zeithaml et. al. (1990) namely tangible, reliability,responsiveness, assurance, and empath. Data was collected through interviews, observation, documentation. and literature study. The results of this study provide the fact that there are still many problems with public transportation facilities and infrastructure in Surabaya, such as seats that are not suitable for use, damaged air conditioning, passenger transportation that does not meet capacity, damaged road conditions, etc. The next fact is that the public transportation service mechanism in Surabaya has been made transparent and simple by using the GoBis application for payments. However, public transportation services in Surabaya still have inhibiting factors, such as the GoBis application which is not available for IOS users, guide tiles and braille signs at bus stops for the disabled are not yet available. Based on this, the strategies that can be used by the Surabaya City Transportation Department are the development of traffic engineering using the e-dishub technology system, government regulations regarding the provision of public transportation subsidies and the development of facilities and infrastructure in the transportation sector